Pengembangan Mobile Learning IPA (MLI) Sasirangan Materi Pencemaran Lingkungan untuk Peserta Didik SMP - Putri Diana Amrita; Heru Kuswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
This study is aimed at: (1) creating Sasirangan Science Mobile (MLI Sasirangan) Learning product for junior high school students and (2) determining the feasibility level of MLI Sasirangan according to experts, practitioners, academics, and the response of students in limited trial test as users. The type of this research is research and development (R&D). Furthermore, the result of this research shows that: (1) Android-web-application-based MLI Sasirangan was created from Learning Management System (LMS) Moodle. The material was delivered by integrating the waste of typical South Kalimantan fabric making with the environmental pollution material and learned online; (2) based on the assessment result from media and material experts, this product obtained a value of 4.73 and 4.48 with a feasibility percentage of 94.6% and 89.56%. Meanwhile, the evaluation result from practitioners and peers, the values obtained were 4.45 and 4.64. Moreover, from the limited trial test, this product obtained a value of 4.47 with the percentage of feasibility is of 89.00%, 92.80% and 89.40% respectively. Therefore, it can be concluded that MLI Sasirangan which has been developed is considered feasible with very good criteria to be used as science learning media. Keywords: Mobile learning, android, sasirangan, science.